The formation of children's healthy lifestyle in the educational process is the main issue - Zhapanova, R.; Mardahaev, L.; Kertaeva, K.; Ishanov, P. (KSU publ., 2020)
The article is devoted to actual issues of schoolchildrens' health, optimization of the educational process, the formation of the value of health and a healthy lifestyle. In addition, the article discusses the issues of healthy lifestyles and the problems of mainstream health care in modern educational institutions. Currently, during the reform of secondary schools of the Republic of Kazakhstan there are many issues related to the health problems of students associated with the transition to twelve-year education. In this regard, in the modern education system, new, innovative methods of teaching and educating younger students on the formation of a healthy lifestyle were considered, ways of forming a healthy lifestyle were proposed. Particular attention was paid to the formation and organization of healthy lifestyle, and practical recommendations were given. Optimal conditions for healthy lifestyles are formulated. One of the areas of educational work at school is cognitive activity, which contributes to the formation of an active life position of the schoolchildren. It is a means of creating a healthy lifestyle. The methods and techniques of forming a healthy lifestyle were analyzed, the effectiveness of forming a healthy lifestyle of younger students was proved.
Keywords: healthy lifestyle; well-being; education; modern teacher; health